2021
DOI: 10.3390/genes12040483
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity and Evolution of Sex Chromosomes in Frogs

Abstract: Frogs are ideal organisms for studying sex chromosome evolution because of their diversity in sex chromosome differentiation and sex-determination systems. We review 222 anuran frogs, spanning ~220 Myr of divergence, with characterized sex chromosomes, and discuss their evolution, phylogenetic distribution and transitions between homomorphic and heteromorphic states, as well as between sex-determination systems. Most (~75%) anurans have homomorphic sex chromosomes, with XY systems being three times more common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 113 publications
(193 reference statements)
0
56
0
Order By: Relevance
“…Nevertheless, the rate of chromosomal rearrangements in amphibians was previously estimated to be less frequent compared to mammals [ 107 ]. Recent genomic studies have shown that chromosomes experienced high levels of fusion type rearrangements in salamanders and frog species [ 108 , 109 ]. Further studies are required to investigate whether this high-level tendency of chromosomal rearrangements in amphibian genomes can trigger the formation of microchromosomes, and how such forces might impact their evolution.…”
Section: Microchromosome Distribution In Vertebrate Lineagementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the rate of chromosomal rearrangements in amphibians was previously estimated to be less frequent compared to mammals [ 107 ]. Recent genomic studies have shown that chromosomes experienced high levels of fusion type rearrangements in salamanders and frog species [ 108 , 109 ]. Further studies are required to investigate whether this high-level tendency of chromosomal rearrangements in amphibian genomes can trigger the formation of microchromosomes, and how such forces might impact their evolution.…”
Section: Microchromosome Distribution In Vertebrate Lineagementioning
confidence: 99%
“…In addition to amniotes, other vertebrate genomes including some primitive amphibians and lower bony fish also represent a highly dynamic number of microchromosomes. The karyotypes of Cryptobranchidae and Hynobiidae families of amphibians can carry 2 n chromosomes ranging from 56–66, with 14–19 pairs of microchromosomes [ 11 , 69 ] Chromosomal linkage homologies, as well as fission and fusion rearrangements have been detected between avian and amphibian genomes, and comparative mapping showed a considerable amount of homology between different macro- and microchromosomes [ 109 , 288 ]. Microchromosomes can also be found in chondrostean and holostean fish (2 n = 46–112), related to crossopterygian fish that gave rise to terrestrial vertebrates 280 Mya, with genomes similar in size to birds [ 53 ].…”
Section: Highly Conserved Linkage Homology Between Macro- and Microchromosomes And The Fusion-fission Model Of Vertebrate Evolutionmentioning
confidence: 99%
“…Recombination suppression evolved numerous times in a wide range of organisms, even sometimes within the same genus and at different times [56,57]. Moreover, the evolutionary strata present in some sex chromosomes represent stepwise extension events of recombination suppression that occurred at different time points; e.g., the four successive steps of recombination suppression on the mammalian Y chromosome [52,58,59].…”
Section: Introductionmentioning
confidence: 99%
“…However, a formal study of the tempo of degeneration requires data from a large number of independent events of recombination suppression of varying ages, which has not been available so far (Charlesworth 2021). Recombination suppression has however evolved numerous times in a wide range of organisms, even sometimes multiple independent times within the same genus (Ma and Veltsos 2021; Mrackova, et al 2008). Moreover, the evolutionary strata present in some sex chromosomes represent stepwise extension events of recombination suppression that occurred at different time points; e.g ., the four successive steps of recombination suppression on the mammalian Y chromosome (Lahn and Page 1999; Ross, et al 2009; Skaletsky, et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As a first application of the new linkage map, we identified the sex determining (SD) region in Bombina , which together with the majority of amphibians lack heteromorphic sex chromosomes ( Eggert 2004 ; Ma and Veltsos 2021 ). Diplotype estimates were coupled with histological estimates of F2 progeny sex.…”
Section: Introductionmentioning
confidence: 99%